SWOT Analysis of Futsal Sports Achievement Development at Futsalnisti Binjai Club (Fnb) - Eka Abdurrahman; Ika Endah Puspita Sari; Liliana Puspa Sari; Haikal Ariq Habibi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
Coaching is a factor that plays an important role in the world of sports, especially futsal, futsal coaching needs to be done as early as possible through talent scouting and scouting, nursery, sports education and training based on science and technology effectively and efficiently, due to whether the sports world itself is developing or not. The Futsalnisti Binjai futsal club (FNB) in Binjai City is one of the platforms used as a means of fostering and developing talent in the sport of Futsal, the aim of which is to help players achieve peak performance. Therefore it is necessary to analyze strength, weakness, opportunity, threats. This type of research is included in the qualitative descriptive research. The method used is SWOT (strength, weakness, opportunity, threat). Sources of research data were obtained from interviews with club administrators, coaches, athletes who excel at U-21, and parents of guardians of FNB futsal club athletes. Data collection techniques using (1) interviews (2) observation (3) documentation. The results of the study can be seen, (1) strengths include: good management according to job descriptions, licensed or certified trainers, motivation and support, talented and accomplished athletes, nursery, the relationship between administrators, coaches, players, and parents, ( 2) weaknesses include: lack of facilities and infrastructure, sources of funds, management policies for administrators, coaches, players, (3) opportunities include: being a reference for other futsal teams for the coaching process, being able to produce good players physical, mental and skill, achieve even better performance and players have high flying hours, with good performance can add a lot of additional funds from various sponsors, (4) threats include: jealousy occurs from other futsal teams due to many players who join the FNB Futsal Club.